Dynamic Mechanical Behavior and Numerical Simulation of Frozen Soil under Impact Loading - Dan Zhang; Zhiwu Zhu; Zhijie Liu (Shock and Vibration)
Split Hopkinson pressure bars (SHBP) were used to perform impact experiments on frozen soil under various impact velocities and temperatures to analyze the effect of these parameters on the mechanical behavior of the soil. Based on the Holmquist-Johnson-Cook constitutive model, the dynamic mechanical properties under impact loading were analyzed. The SHPB experiments of frozen soil were also simulated using the finite element analysis software LS-DYNA, and the simulation results were similar to the experimental results. The temperature effect, strain rate effect, and the destruction process of the frozen soil as well as the propagation process of stress waves in the incident bar, transmission bar, and frozen soil specimen were investigated. This work provides a good theoretical basis and technical support for frozen soil engineering applications.